Gdzie jest środek Polski, czyli o problemie wyboru reprezentanta zbioru - Maciuk, Arkadiusz (Where is the middle of Poland or how to choose the representative of the set, 2007)
In many cases a problem appears how to choose a point which would represent a set in the best way. Depending on the context such a point is called middle of the set, parameter of location, estimator, best representative or simply a representative of a set. There are many ways of choosing such a representative. What is essential is that the choice as such is preceded by setting the criteria of choice which depend among others on the type of the issue. A representative commonly used in probability issues should not be automatically used in determinism issues - as finding optimal location. In the article various representatives are presented as well as techniques and determinants of their choice. Specifically, local representatives are discussed - such that are dependent more on measure than size of the analyzed set. These issues are illustrated by the set of Polish communes. Where is the geographical middle of Poland? With which criteria can the city of Warsaw be the middle? Can they be set so that e.g. the city of Katowice is one? These are some interesting questions which can be answered analyzing the issues of choosing the representatives of the set.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 202-210